The usability of recycled carbon fibres in short fibre thermoplastics: interfacial properties - Burn, D.T.; Harper, Lee Thomas; Johnson, M.; Warrior, N.A.; Nagel, U.; Yang, L.; Thomason, J. (Springer, 2016)
The objective of this study was to investigate the feasibility of combining discontinuous recycled carbon fibres with polypropylene, to produce a low-cost, high specific stiffness material for high-volume applications. The inherent low affinity of carbon fibre and polypropylene motivated a detailed study of the surface characteristics of carbon fibre and interfacial behaviour between the two materials, using the microbond test. The effects of removing the sizing from the fibres, as well as introducing a maleic anhydride-grafted polypropylene coupling agent, were extensively investigated. Polypropylene was found to degrade when prepared under atmospheric conditions; therefore, it was necessary to form droplets under nitrogen. Removal of the sizing from the fibre using pyrolysis and solvolysis techniques altered the surface morphology of the fibre and increased the interfacial shear strength (IFSS) by 4 and 33 %, respectively. A more significant improvement in the fibre–matrix adhesion was achieved by adding a maleic anhydride coupling agent at 2 wt%, which increased the IFSS by 320 %.